Analisis Wacana Kritis Pemberitaan Alinea.id Tentang Hizbut Tahrir Indonesia (HTI) yang Menolak Mati - Rahmat Hidayat (STBA LIA - Jakarta, 2020)
This research focuses on the story of the existence of HTI in Indonesia although it has already been banned by the government. Using CDA Norman Faiclough’s model, this research study the text analysis, discourse practice on production and consumption of the text and sociocultural practice. This research uses one news article from alinea.id entitled HTI Menolak Mati: Bermutasi, Menyebar, dan Bergerak di Bawah Tanah as a research object and using qualitative methods and critical paradm. Result of this research shows the text on alinea.id entitled HTI Menolak Mati: Bermutasi, Menyebar, dan Bergerak di Bawah Tanah construct using discourse unit namely Headline, Orientation, Sequence of events, and closing. Modality is used to manifest ideology in the text.